A Comprehensive Analysis of the Application of TPACK in Tenth-Grade Students’ Writing Practice: English - Nilam Kantang Ratu; Tahrun; Masagus Firdaus (Journal of English Development, 2024)
Writing is a skill that is needed by the students nowadays, which is the capacity of an English teacher to become a significant element to improve students’ understanding in writing, especially in the use of Merdeka curriculum. But the phenomenon of teacher is still unfamiliar with the Merdeka curriculum and its content knowledge, Technological, Pedagogical, and Content Knowledge (TPACK) is still infrequently applied, while the use of technology should be implemented in learning process of Merdeka curriculum. To face this phenomenon, this study focused on the integration, implementation, and result of TPACK itself in writing skill. This study was a case study where a qualitative descriptive method to assess the result. There was an English teacher who became the main participant to be observed, which she taught class X Akuntansi Keuangan Lembaga (AKL) whom the researcher observed. The data was conducted by using observation, interview, questionnaire, and documentation. The result showed that TPACK was implemented by teachers and had a positive impact on students’ writing.  In addition, the integration of technology, pedagogy, and content of teaching constructed the implementation of TPACK. It affected the students’ skills to get good writing that was assessed by the teacher’s writing rubric.